Diversity and Condition Analysis of Coral Reef in Lahu Besar Island, Ringgung, Pesawaran District - Utomo, Deny Sapto Chondro; Yulianto, Herman; Yuliana, Darma (AQUASAINS, 2016)
The aims of this study is to determine the diversity and condition of coral reef ecosystems in the island of Lahu Besar, Ringgung. Some parameters were observed are percent cover and condition of coral reefs, composition and density of coral species, and water quality include salinity, temperature, clarity, waters current, pH, and sedimentation. The surface temperature at the time of observation average of 30-31 oC and salinity of sea water an average of 32 - 34 o/oo. The clarity in the study area is 5 meters. Distribution of reefs founded in the Lahu Besar bay to Â± 10 m in depth. The substrate dominated by sand and dead coral. The Percent cover of live coral is about 10.5 to 52.9%. The other form of covered substrate consist of Enhalus acoides, Sargassum echinocarpum andHalimeda micronesica. The results showed that the density of the dominant species of coral stones at each station is about 0.1 to0.63 ind / m. The coral reef was dominated in Station I was kind of Acropora nobilis, Station II is Montipora ï¬‚orida, and Station III is Acropora nobilis and Acropora formosa. Diversity index valuesÂ  obtained at each station is about 0.80 to 1.68.